Intersections of Mind and Machine: Navigating the Nexus of Artificial Intelligence, Science Education, and the Preparation of Pre‑service Teachers - Cooper, Grant; Tang, Kok-Sing; Fitzgerald, Angela (Springer Nature, 2025)
The rapid advancement of generative artifcial intelligence (GenAI) is reshaping various sectors, including education. This editorial explores the intersections of AI, science education, and the preparation of pre-service teachers (PSTs), questioning whether GenAI represents a truly transformative technology or merely the latest iteration of an educational hype cycle. While previous technological innovations—such as radio, television, and computers—were initially heralded as revolutionary, their impact on education has varied signifcantly. The emergence of GenAI, particularly large language models, introduces new possibilities for personalised learning, digital tutoring, and adaptive content generation, yet its integration into educational practice remains uneven. Despite growing societal reliance on GenAI, a substantial proportion of in-service teachers report limited use, citing a lack of training and institutional policies as key barriers. In contrast, research suggests that PSTs are already engaging with GenAI tools for lesson planning, content summarisation, and assessment preparation. This edito rial underscores the need for initial teacher education (ITE) programmes to provide structured support, ensuring that PSTs develop both technical profciency and critical AI literacy. Ethical concerns—such as data privacy, algorithmic bias, and epistemic authority—must also be central to teacher training. Focusing on science education, this special issue examines the opportunities and challenges of GenAI integration. The contributions explore PSTs’ perceptions, competencies, and preparedness to implement AI-driven tools in their teaching, addressing themes such as inquiry-based learning, pedagogical content knowledge, and the evolving role of educators in AI-powered classrooms. The discussion highlights the necessity of balancing technological innovation with critical refection, equipping future teachers to navigate the complexities of AI in education responsibly. This editorial aims to advance the dialogue on GenAI’s role in teacher preparation, urging educational institutions to proactively support PSTs in harnessing its potential while fostering a critical, ethical, and pedagogically sound approach to AI integration in science education.